The C-RORC PCIe card and its application in the ALICE and ATLAS experiments - Borga, Andrea; Costa, F.; Crone, G. J.; Engel, Heiko; Eschweiler, Dominic; Francis, D.; Green, B.; Joos, M.; Kebschull, Udo; Kiss, T.; Kugel, Andreas; Vazquez, J. G. Panduro; et al. (Journal of Instrumentation, 2015)
The ALICE and ATLAS DAQ systems read out detector data via point-to-point serial links into custom hardware modules, the ALICE RORC and ATLAS ROBIN. To meet the increase in operational requirements both experiments are replacing their respective modules with a new common module, the C-RORC. This card, developed by ALICE, implements a PCIe Gen 2 x8 interface and interfaces to twelve optical links via three QSFP transceivers. This paper presents the design of the C-RORC, its performance and its application in the ALICE and ATLAS experiments.
Gesehen am 19.06.2020